The diagnostic value of optic disc evaluation in acute elevated intracranial pressure - Steffen, Heimo; Eifert, Birgit; Aschoff, Alfred; Kolling, Gerold; Völcker, Hans Eberhard (Ophthalmology, 1996)
Purpose: Ophthalmologists often are asked to evaluate the optic disc for evidence of acute increased intracranial pressure (ICP). The authors studied the incidence of papilledema in a population of patients with a documented acute increase in ICP. Methods: Included in this study were 37 patients with acute elevated ICP due to a spontaneous hemorrhage or craniocerebral trauma. In all patients, the ICP was monitored continuously. Fundus examination was performed twice daily on at least 7 consecutive days. Results: According to the level and duration of the ICP, the patients were divided into three groups. Group 1 included 13 patients who had a slightly elevated ICP (range, 20-30 mmHg) on at least 3 consecutive days. In this group, 3 of 13 patients demonstrated venous congestion on the fifth or sixth day. No swelling of the optic disc was seen in this group. Group 2 included seven patients with an elevated ICP, with values ranging from 30 to 70 mmHg lasting for at least 3 consecutive days. In this group, one patient had a blurred disc margin on the sixth day. Group 3 included 17 patients with shortlasting ICP values, ranging from 30 to 60 mmHg for less than 72 hour. Neither papilledema nor abnormalities of fundus vessels were seen in this group. Conclusion: Papilledema in acute elevation of ICP is an uncommon event. Its absence does not preclude the presence of ICP elevation.
Elektronische Reproduktion der Druck-Ausgabe 3. Oktober 2013
Gesehen am 02.11.2023